Knockdown of Two Iodothyronine Deiodinase Genes Inhibits Epinephrine-Induced Larval Metamorphosis of the Hard-Shelled Mussel Mytilus coruscus - Shi, Xue; Wang, Yu-Qing; Yang, Yue-Ming; Li, Yi-Feng (Frontiers in Marine Science, 2022)
The metamorphosis process is a critical life-changing event for marine invertebrate planktonic larvae to transform into benthic adults, which is crucial for the shellfish bed’s ecosystem stability and seed production in aquaculture. The mechanism of neuroendocrine regulation in the larval metamorphosis of bivalves remains ambiguous. In the present study, the expression of two deiodinase genes, McDx and McDy, was analyzed by whole-mount in situ hybridization at four larval stages in the hard-shelled mussel Mytilus coruscus. The McDx and McDy localized in visceral tissues, nervous system, mantle, and velum, indicating that two deiodinase genes are essential for larval development in M. coruscus. Knockdown of the McDx and McDy in the pediveliger larvae of M. coruscus using electroporation of siRNA significantly (p < 0.001) reduced McDx and McDy expression. McDx and McDy knockdown reduced larval metamorphosis in 45% and 49% of the pediveliger larvae induced by epinephrine (EPI). It is hypothesised that the knockdown effects of McDx and McDy repress metamorphic induction rather than larval viability, which does not elicit a lethal effect. The present study corroborates a synergistic action of the adrenergic and thyroid hormones signalling pathway in M. coruscus, and suggests the role of McDx and McDy in larval development and metamorphic transition.